(3GdHgLI GdhQOis - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s ((3YHOGddg Hf eMeO Hf CHj HcQ Hf YHOGdQMef GdWGgQ s)
(3ChdgG (B:s
(3hHYO aGdYde YXje GdefRdI bO GUWai Gddg NjGQ GdNdb dg s
(3BNQgG (B:s
(3hGdCd hGdUMH HgPG CNJe fXei hGddg JYGdi CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
Keywords: (3CUhd Gdabgs